Political Satire and British-American Relations in Five Decades of Doctor Who. - DIPAOLO, MARC EDWARD (Journal of Popular Culture (John Wiley & Sons, Inc.), 2010)
In this article the author discusses aspects of "Doctor Who," a British science fiction television program developed by Russell T. Davies, the head writer and producer. The article notes that despite the success of the program, begun in 2005, there has been a rejection of it in some quarters, notably from enthusiasts of the first iteration of the program. A number of topics are addressed including the political satire contained in the program, the assertion that some of the characters and situations are anti-American, and the actors who have played the title character.